A quantitative analysis of the identification of personality traits in engineering students and their relation to academic performance - Cárdenas Moren, Camila; Crawford Augant, Kathleen; Crawford Labrin, Broderick; Soto de Giorgis, Ricardo; de la Fuente-Mella, Hanns; Peña Fritz, Álvaro; Valenzuela Saavedra, Matías; Hermosilla Monckton, Pamela; Álvarez Castelli, Lorena (Studies in higher education (Dorchester-on-Thames), 2020)
This study focuses on identifying personality traits in engineering students and testing whether they are related to academic performance. In addition, the importance of the personality construct in the educational and vocational training context was studied. A sample of 235 students from the Construction Engineering and Computer Engineering Schools of the Pontifical Catholic University of Valparaíso was used. Through correlation and econometrics analysis, the results obtained indicate that there is a relation between academic performance and the personality traits of extraversion, openness and conscientiousness. In addition, these results led to characterization of students based on their personality traits and provided elements that may enhance the development of an effective personality that allows students to successfully face their environment, playing an important role in the educational process.